2016
DOI: 10.2147/ott.s89967
|View full text |Cite
|
Sign up to set email alerts
|

PI3K inhibitors as new cancer therapeutics: implications for clinical trial design

Abstract: The PI3K–AKT–mTOR pathway is frequently activated in cancer. PI3K inhibitors, including the pan-PI3K inhibitor buparlisib (BKM120) and the PI3Kα-selective inhibitor alpelisib (BYL719), currently in clinical development by Novartis Oncology, may therefore be effective as anticancer agents. Early clinical studies with PI3K inhibitors have demonstrated preliminary antitumor activity and acceptable safety profiles. However, a number of unanswered questions regarding PI3K inhibition in cancer remain, including: wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
155
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(166 citation statements)
references
References 37 publications
(48 reference statements)
2
155
0
5
Order By: Relevance
“…Inhibition of PI3K has particularly become a highly desirable avenue for pharmacological intervention, with dozens of PI3K inhibitors, including taselisib, copanlisib, pictilisib, buparlisib, and others, being in clinical trials and idelasib being approved for a set of leukemias and lymphomas (4,35). Although initially very promising, targeted inhibition of PI3K often suffers from the development of resistance to drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of PI3K has particularly become a highly desirable avenue for pharmacological intervention, with dozens of PI3K inhibitors, including taselisib, copanlisib, pictilisib, buparlisib, and others, being in clinical trials and idelasib being approved for a set of leukemias and lymphomas (4,35). Although initially very promising, targeted inhibition of PI3K often suffers from the development of resistance to drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This observation clearly illustrates that targeting a single protein/ pathway may not provide a long-lasting therapeutic effect because of the highly heterogeneous nature of cancer, in which multiple signaling cascades are impaired, and that alternative approaches with the focus on synergistic inhibition of more than one deregulated or compensating pathway have to be developed. Currently, a number of clinical trials are ongoing to apply PI3K inhibitors in combination with other drugs (35).…”
Section: Discussionmentioning
confidence: 99%
“…PKI-587, a potent novel dual inhibitor of PI3K and mTORC1/C2; inhibitors of mTORC1 and mTORC2, e.g. AZD2014, OSI-027) warrant further investigation based on preclinical studies (Freitag et al 2016, Massacesi et al 2016, Vandamme et al 2016. Another promising combination therapy is metformin and everolimus.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…both broad and selective inhibitors will provide data on distinct efficacies (Massacesi et al 2016).…”
Section: :11mentioning
confidence: 99%
“…Another strategy is to find the optimal administration [4] . From our experience, we found that the dose of PI3K inhibitors administered intratracheally was about 50-60 folds less than that given orally to gain the same efficacy, when PI3K inhibitors were used to prevent and treat the inflammation-induced acute lung injuries [5] .This was an initial study to define the therapeutic windows of PI3K inhibitors between local and systemic drug deliveries in non-cancer pathology.…”
Section: Discussionmentioning
confidence: 99%